CK-3, A Novel Methsulfonyl Pyridine Derivative, Suppresses Hepatocellular Carcinoma Proliferation and Invasion by Blocking the PI3K/AKT/mTOR and MAPK/ERK Pathways - Wu, Qiong; Liu, Tian-yi; Hu, Bai-chun; Li, Xiang; Wu, Yu-ting; Sun, Xiao-tong; Jiang, Xiao-wen; Wang, Shu; Qin, Xiao-chun; Ding, Huai-wei; Zhao, Qing-chun (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is an aggressive tumor with a poor prognosis that highly expresses phosphatidylinositol 3-kinase (PI3K) and mitogen-activated protein kinase (ERK). The PI3K/AKT/mTOR and MAPK/ERK signaling pathways play a crucial role in HCC tumor formation, cell cycle, apoptosis and survival. However, no effective targeted therapies against these pathways is available, mainly due to the extensive and complex negative feedback loops between them. Here we used CK-3, a dual blocker of the PI3K/AKT/mTOR and MAPK/ERK pathways, against HCC cell lines to verify its anti-tumor activity in vitro. CK-3 exhibited cytotoxic activity against HCC, as demonstrated with MTT and colony formation assays. The anti-metastatic potential of CK-3 was demonstrated with wound healing and cell invasion assays. The ability of CK-3 to block both the PI3K/AKT/mTOR and MAPK/ERK pathways was also confirmed. CK-3 induced the apoptosis of Hep3B cells, while Bel7402 cells died via mitotic catastrophe (MC). Simultaneous PI3K/AKT/mTOR and MAPK/ERK pathway inhibition with CK-3 may be superior to single pathway monotherapies by inhibiting their feedback-regulation, and represents a potential treatment for HCC.